Overview of pelletisation technology and pellet characteristics from maize residues - Pakamon Pintana (2020)
Copyright © 2020, AIDIC Servizi S.r.l. Maize is a popular field crop in Thailand for animal feed production. The country dedicates more than six million hectares to maize cultivation, and its total output amounts to about five million tons. The harvest of maize results in three primary residues: roots, stalks, and leaves. Over 80 % of these residues are disposed of in the cultivated area itself, usually by open burning. This practice releases large amounts of pollutants (such as the hazardous particulate matter known as PM2.5) into the atmosphere. Pelletisation represents one promising alternative to such strategies as open burning. The main objective of this study is to provide an overview of the pelletisation process in order to guide future attempts to increase efficiency and sustainability in maize pellet production. Thai standards for the production of pellets are compared with international standards, and the effects of differences in pellet composition on combustion efficiency are discussed. The results of this study can serve as a guideline for spearheading zero-waste agriculture initiatives and promoting the use of renewable resources like pellets for utilisation in biomass power plants, per the recommendations in the Alternative Energy Development Plan (AEDP 2012-2021).